Excitation-time-independent seismic tomography for blast-induced rock damage characterization and its application - Shuaiyang Fu; Yafei Hao; Pinghe Sun; Hongbing Li; Zhendong Leng; Xianhang Huang; Tengfei Li; Qiang Gao; Haibo Li; Xiaofeng Li (Computers and Geotechnics, 2026)

Unraveling the synergistic mechanism of H2SO4/H2O2 system enabled by a dynamic dosing strategy for sustainable recycling of spent Li-ion batteries - Shukai Miao; Minsheng Fu; Xinhai Li; Bichao Wu; Zhixing Wang; Guangchao Li; Xiaoping Zhou; Tao Chen; Faping Zhong; Hongbing Liu; Jiexi Wang (Hydrometallurgy, 2026)

Ambient-air fabrication of high-performance thick-film organic solar cells enabled by solid additive engineering - Kun Li; Cunbin An; Yuan Yao; Jianbin Zhong; Bin Hu; Wei Zhang; Yishi Wu; Bowei Xu; Dianyi Liu; Guanghao Lu; Qing Liao; Xiaozhang Zhu; et al. (Chemical Engineering Journal, 2026)

Heavier sediment pollution by per- and polyfluoroalkyl substances (PFASs) in tropical coasts compared to temperate regions: An overlooked hotspot - Hui Xie; Shiya Gu; Yang Cui; Jianwei Dong; Hongbing Wang; Guowei Fu (Journal of Environmental Sciences, 2026)

Polychlorinated biphenyl pollution as an unintentional major contaminant in the Pearl River Delta, China - Hongbing Wang; Chenglong Wei; Guowei Fu; Daheng Zhang; Miao Fu; Junyi Jiang; Yue Long; Yanwei Song (Environmental Research, 2025)

Mn/CeO2 contains enriched surface lewis acid sites and pore structures accelerated catalytic oxidation of propane at low temperature - Zijian Zhang; Yuxuan Ou; Zhijian Fu; Jiayu Ying; Yunjie Zong; Boyi Lang; Chenghan Yang; Yubo Zhou; Xuyu Wang; Hongbing Ji (Fuel, 2024)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Research on comprehensive assessment of coastal erosion intensity based on multi index method - Guowei Fu; Mingguang He; Xiaofeng Chen; Miao Fu; Yanwei Song; Chenglong Wei; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
The intensity of coastal erosion is a measure of the strength of erosion processes affecting coastal areas. Traditionally, assessments of coastal erosion intensity have relied on singular indices, such as the rate of shoreline retreat or erosion, often prioritizing higher rates over lower ones. This approach, however, lacks comprehensive consideration and scientific rigor. In this study, we adopt a more holistic approach by examining the Qionghai-Wanning coast on the eastern side of Hainan Island. We selected four indices that reflect local conditions and influence coastal erosion strength: Annual rate of shoreline change (T1), Beach annual down-cutting rate (T2), Beach slope (T3), Average particle size of the beach (T4). These indices were used to comprehensively evaluate the erosion intensity of the Qionghai-Wanning coast. The evaluation results categorized the study area into six grades: serious erosion (3.45%), strong erosion (6.90%), erosion (20.69%), micro erosion (44.38%), stabilization (20.69%), and accretion (3.45%). The findings indicate that, under the broader environmental trends of global warming and rising sea levels, most sandy coasts exhibit micro-erosion intensity. Areas experiencing strong and serious erosion are predominantly influenced by human activities, such as those occurring in promenade bays, artificial islands, and harbors. To further understand the relationship between these factors and erosion intensity, we employed the Spearman correlation coefficient method. The analysis revealed that the T1 and the T2 are the primary factors influencing coastal erosion intensity, with the T4 serving as a secondary factor. These factors collectively impact the force and energy absorption of the coast through wave and tidal actions, ultimately determining the intensity of coastal erosion. The multi-index assessment method for coastal erosion intensity demonstrated an accuracy of 82.75%, providing a scientific basis for the management, protection, and restoration of coastal areas.

Assessment of the community status of seagrass bed and its relationship with environmental characteristics in Wenchang, Hainan Island, China - Miao Fu; Junyi Jiang; Dacheng Wang; Guowei Fu; Yanwei Song; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
As one of the typical coastal ecosystems, seagrass bed has important ecological service functions. In order to enrich the basic data of multispecies tropical seagrass beds, the main controlling factors affecting the community status of seagrass were identified. In this study, the species, distribution and community characteristics of seagrass in Wenchang were investigated at five stations in 2023, and Spearman correlation analysis and Redundancy analysis were used to investigate the relationship between seagrass and environmental characteristics. The results showed that there were 7 species of seagrass belonging to 5 genera in 2 families along Wenchang coast, including Enhalus acoroides , Thalassia hemprichii , Cymodocea rotundata , Cymodocea serrulata , Halophila ovalis , Halophila minor and Halodule uninervis . The distribution of seagrass beds in Wenchang showed an obvious trend of degradation. Except for the relatively stable of seagrass beds in the central part of Wenchang, the seagrass beds on both the north and south sides decreased significantly, and the coverage of seagrass beds decreased from 24.31% in 2016 to 21.0% in 2020, and further decreased to 20.67% in 2023. The data showed that the coverage and aboveground biomass of seagrass were significantly positively correlated with temperature, and the density of seagrass was significantly positively correlated with DO, but significantly negatively correlated with COD. In addition, increased nutrient salts in the water column could negatively affect seagrass bed. In order to promote the sustainable development of seagrass ecosystem and enhance the stability of seagrass habitat, it is suggested to rationally plan the aquaculture scale of the surrounding area; flexibly manage the rake snail, rake clam and other fishing activities, appropriately reduce the frequency of mining; and scientifically plan marine engineering to reduce the damage to seagrass bed.

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Exploring the nonlinear association between agri-environmental regulation and green growth: The mediating effect of agricultural production methods - Hongbing Zhu; Lihua Yang; Changxin Xu; Tianbo Fu; Jianting Lin (Journal of Cleaner Production, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Metatranscriptomic insights into the microbial metabolic activities during an Ulva prolifera green tide in coastal Qingdao areas - Xinyi Wang; Hao Yu; Yan Li; Qianru Fu; Hongbing Shao; Hui He; Min Wang (Environmental Pollution, 2024)

Dynamics of the water environment in a water quantity-quality-soil model of China’s Yellow River basin: imbalance and driving factors - Lihua Yang; Changxin Xu; Hongbing Zhu; Tianbo Fu (Environmental Monitoring and Assessment, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Recent advances in alleviating food allergenicity through fermentation - Xiaowen Pi; Yili Yang; Yuxue Sun; Qiang Cui; Yin Wan; Guiming Fu; Hongbing Chen; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Genome-wide SNP analysis reveals the selection signatures of two indigenous buffalo breeds in Sichuan - Wei Wang; Donghui Fang; Yi Shi; Fang He; Jia Gan; Maozhong Fu; Xiaodong Deng; Tao Zhang; Hongbing Shen; Shengchao Zhong; Yueda Aguo; Luxi Chen; et al. (Conservation Genetics Resources, 2022)
Sichuan Province spawned abundant of indigenous buffalo varieties, which probably harbor valuable gene resources beneficial to the genetic improvement of buffalo. However, limited genetic information was publicly available. To better understand their selection signatures between different populations, we performed a restriction site-associated DNA sequencing (RADseq) to explore genome-wide SNPs among two indigenous breeds of Sichuan buffaloes. As a result, a total of 2,110,077 high-quality SNPs were finally obtained. Population genetic analysis indicated a obviously genetic differentiation between two breeds. The detection of selective genes showed that 995 and 910 protein-coding genes underwent positive selection in Yibin buffalo (GYBS) and Dechang buffalo (XCS). Further functional analysis revealed distinctly discrepant selection in two breeds. Candidate genes that positively selected from Yibin buffaloes have mainly occurred in functions closely related to meat quality, complex living environment adaption capability, and disease resistance. While they were significantly enriched in cell proliferation and cell components in Dechang buffalo, indicating the selection pressure primarily derived from the requirement of organism growth and development speed during breed formation. Our dataset constitutes a promising reservoir of genome-wide SNP markers of Sichuan buffaloes and provides potentially traits selected in different local populations. Such comprehensive genetic resources offer an unprecedented opportunity for genetic association analysis of economically important traits and precision breeding programs in buffaloes.

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Bioassay-guided extraction of crude fucose-containing sulphated polysaccharides from Sargassum fusiforme with response surface methodology - Zhifei Fu; Haihua Li; Hongbing Liu; Shuman Hu; Yueying Li; Mengxue Wang; Huashi Guan (Journal of Ocean University of China, 2016)

Analysis of urbanization based on center-of-gravity movement and characteristics in Songhua River basin of China and its southern source sub-basin between 1990 and 2010 - Xiao Fu; Yuan Shen; Rencai Dong; Hongbing Deng; Gang Wu (Chinese Geographical Science, 2016)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Phenotypic characterization of craniofacial bone marrow stromal cells: unique properties of enhanced osteogenesis, cell recruitment, autophagy, and apoptosis resistance - Weijie Dong; Jie Ge; Ping Zhang; Yu Fu; Ziwen Zhang; Jie Cheng; Hongbing Jiang (Cell and Tissue Research, 2014)

Contribution of SATB2 to the stronger osteogenic potential of bone marrow stromal cells from craniofacial bones - Ping Zhang; Jie Men; Yu Fu; Tengfei Shan; Jinhai Ye; Yunong Wu; Zhenjiang Tao; Laikui Liu; Hongbing Jiang (Cell and Tissue Research, 2012)